HUKUMAN CAMBUK TERHADAP KONTROL SOSIAL - Ferizal, Indis (IAIN Langsa, 2019)
Caning applied in Aceh is one of the social controls and the form of punishment is expected to fulfill the philosophical, juridical and sociological tendencies of legal awareness. Caning is one form of punishment that is also expected to foster a lawful attitude and the creation of an orderly society. According to Islamic law that punishment is for the benefit of the Ummah and educate the person of the perpetrator of the crime. Basically It is not easy to do efforts to increase legal awareness and the development of a legal culture in the community without encouragement from individual communities themselves. This should be of particular concern by the government to be more serious in conducting socialization so that legal awareness can be understood and implemented by the public properly.